Dietary lipids shape cytokine and leptin profiles in obesity-metabolic syndrome implications: A cross-sectional study. - Sakawrut Poosri; Karani Santhanakrishnan Vimaleswaran; Pattaneeya Prangthip (PLoS ONE)
Background Obesity, characterized by chronic energy imbalance and excessive adiposity, is a key component of metabolic syndrome and is associated with low-grade inflammation and altered adipokine secretion. This study aimed to evaluate the association between dietary fat consumption and its influence on interleukin (IL) and leptin levels in participants with obesity. Methods Using the Asian obesity classification criteria, a cross-sectional study was conducted on 384 adults (18-59 years). Anthropometric measurements by bioelectrical impedance analyzer (BIA), blood biochemistry by colorimetric assay, inflammatory markers and hormones by ELISA test, and dietary intake were assessed by Semi-FFQ. Results Obesity prevalence was 26.1% and 73.90% in males and females, respectively. Participants with obesity exhibited significantly higher inflammatory and hormonal marker levels. Positive correlations were observed between blood lipid, glucose, and tumor necrosis factor-α, IL-6, and leptin levels. Energy, carbohydrate, and sugar intake were positively correlated with leptin levels. High saturated fat intake was associated with increased IL-6 levels (odds ratio = 2.03, 95% confidence interval [CI] = 1.00-4.11, p < 0.047), whereas high total fat intake elevated leptin levels by 2.14-fold (95% CI = 1.12-4.10, p < 0.021) in participants with obesity. Conclusions This study demonstrates significant associations between dietary fat composition, inflammatory markers, and leptin levels in individuals with obesity. These findings suggest that modulating dietary fat intake can be a potential strategy for mitigating obesity-related inflammation and leptin resistance, highlighting the need for targeted nutritional interventions in obesity and metabolic syndrome management.